2022
DOI: 10.1177/18344909221101670
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception, anxiety, and depression among hospital pharmacists during the COVID-19 pandemic: The mediating effect of positive and negative affect

Abstract: This study investigated the impacts of risk perception of COVID-19 on anxiety and depression symptoms among hospital pharmacists in China. We conducted a cross-sectional study with hospital pharmacists during the COVID-19 pandemic in China. Some 4,219 hospital pharmacists completed an online survey including demographic questions, risk perception of COVID-19, General Anxiety Disorder-7, Patient Health Questionnaire-9, and Positive and Negative Affect Schedule. Multivariate regression and mediation analyses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 49 publications
(69 reference statements)
1
14
0
Order By: Relevance
“…However, the findings of an online survey among 1006 healthcare workers including pharmacists (16.8%) in Jordan using Kessler-6 revealed 32% respondents suffered from high distress while only 20% suffered from severe distress [ 11 ]. Similar findings were reported in an online survey in China conducted among 4,219 hospital pharmacists where only 41.9% and 29.4% experienced mild to severe levels of anxiety and depression, respectively [ 19 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the findings of an online survey among 1006 healthcare workers including pharmacists (16.8%) in Jordan using Kessler-6 revealed 32% respondents suffered from high distress while only 20% suffered from severe distress [ 11 ]. Similar findings were reported in an online survey in China conducted among 4,219 hospital pharmacists where only 41.9% and 29.4% experienced mild to severe levels of anxiety and depression, respectively [ 19 ].…”
Section: Discussionsupporting
confidence: 86%
“…Coronavirus disease (COVID- 19) has taken a heavy toll on people's health and lives, afecting severely healthcare systems all across the globe. COVID-19 not only threatened people's health but also gave rise to various psychological complications such as anxiety, depression, and panic disorder [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al (2022) found that negative stress coping among Chinese adolescents during COVID-19 partially mediated the relationship between psychological stress response and aggression, and that this indirect effect was moderated by emotion management skills. Zhang et al (2022) found that negative emotions had a significant indirect effect on discouraged behaviors but a nonsignificant effect on promoted behaviors, and a significant effect on individual behavior but a nonsignificant effect on adherence to local policies. Kulesza et al (2022) compared vaccinated and unvaccinated individuals' assessments of the risk of infection with COVID-19 and the role of unrealistic optimism and social comparison.…”
Section: Behavioral Dimensionsmentioning
confidence: 93%
“…Regarding the mechanisms underlying the onset of emotional stress reactions, a large number of studies have addressed the important role of risk perception on anxiety reactions, and some scholars have even suggested that risk perception plays an important role in each stage of anxiety response generation, presentation, and treatment 16 , 17 . An individual's perception of external objective risks can be referred to as risk perception, which emphasizes the influence of experiences based on intuitive judgments and subjective feelings on an individual's cognition 18 .…”
Section: Introductionmentioning
confidence: 99%